PERANCANGAN SISTEM ABSENSI BERBASIS WEBSITE PADA TK ‘AISYIYAH BUSTANUL ATHFAL 83 MENGGUNAKAN METODE WATERFALL - Cut Fatma Anwar; Fara Yurisus Sakinah; Zahra Amelia; Saprudin (Shofanah Media Berkah, 2023)
In general, the attendance process is carried out through manual stages or using book media. In this study, the implementation of teacher absences at TK 'AISYIYAH BUSTANUL ATHFAL 83 is still being carried out by recording data using book or paper media. This is not effective and efficient because its use can lead to waste and is prone to damage to data stored on paper media. For this reason, an attendance system is needed that can help facilitate the teacher attendance process, so that the attendance process is more effective and efficient. The research method used is observation and literature study. The research method uses the PHP programming language and MySQL database. The model used is waterfall. This research resulted in a new web-based attendance system that is effective and efficient at TK 'AISYIYAH BUSTANUL ATHFAL 83 that is able to manage the attendance process.